(untitled) (Asian Education Studies, 2020)
With an overview of translation history, from the ancient Rome to modern times, from Western countries to Eastern countries, there were heated debates over translation principles or strategies, most of which revolved around the matter of literal translation or free translation. Many famous theorists advocated that literal translation was preferred than free translation; others disapproved that. However, either side failed to have a comprehensive prospective towards translation, because translation is actually a complex framework, involving many elements worth our attention. To do translation studies, the theories shall break the irrational mindset and jump out of dichotomies to gain an overall and objective understanding of translation.